The mechanism of metastasis suppressor gene nm23-H1 involving in the Ras signaling of lung cancer - Xueqin YANG; Yibing YAO; Wen ZHU; Li MA; Daxing ZHU; Wen XIAO; Changlin LI; Jiabao MA; Zhixuan ZHANG; Liwei GAO; Yanping WANG; Qinghua ZHOU (Chinese Journal of Lung Cancer, 2008)
Background and objective It has been confirmed that nm23-H1 gene is one of the tumor metastasis suppressor genes. Up to now, the exact mechanism of nm23-H1 gebe is uncertain. The aim of this study the mechanism of metastasis suppressor gene nm23-H1 involving in the Ras signaling of lung cancer. Methods The wild and mutant typeof pEGFP-nm23-H1 plasmids [WT (wild type), H118F, S120G, P96S, S44A] were transfected into the L9981 lung cancer cell lines through liposome method, and the complex of KSR and nm23-H1 was detected through co-immunoprecipitation and Western blot assay. Results The human KSR could be detected in the nm23-H1 immunoprecipitations in all the trasfected L9981 lung cancer cell lines. But no significant difference of KSR expression was found in the wild and mutantnm23-H1 trasfected cell lines (F =0.190, P =0.938). Conclusion There was a close interaction between nm23-H1 and KSR, which was independent of the nm23-H1 mutation. Nm23-H1 involving in the Ras signaling of lung cancer may be through the KSR gene.